2010
DOI: 10.4037/ajcc2010783
|View full text |Cite
|
Sign up to set email alerts
|

Semirecumbent Positioning in Ventilator-Dependent Patients: A Multicenter, Observational Study

Abstract: Background Positioning of patients is a modifiable risk factor for ventilator-associated pneumonia. Current guidelines for prevention of ventilator-associated pneumonia recommend semirecumbency at 30º, with 45º preferable unless contraindicated. Objective To assess the use of semirecumbency for ventilator patients in Australian and New Zealand intensive care units. Methods In a multicenter, observational study, backrest elevation, mean arterial pressure, use of inotropic agents, enteral feeding, and weaning st… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
21
1
4

Year Published

2011
2011
2023
2023

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 26 publications
(26 citation statements)
references
References 36 publications
0
21
1
4
Order By: Relevance
“…Performing nursing procedures in critical conditions and carrying out nursing interventions in the lateral position hindered the elevation of the HOB. Other factors are a lack of patient comfort, fear of pressure ulcers, and insufficient information regarding raising the HOB for the prevention of VAP (33).…”
Section: Discussionmentioning
confidence: 99%
“…Performing nursing procedures in critical conditions and carrying out nursing interventions in the lateral position hindered the elevation of the HOB. Other factors are a lack of patient comfort, fear of pressure ulcers, and insufficient information regarding raising the HOB for the prevention of VAP (33).…”
Section: Discussionmentioning
confidence: 99%
“…Numerous observational studies [24][25][26] have indicated poor compliance with various evidence-based practice recommendations, indicating that implementation of the recommendations remains a challenge in the ICU. Assessment of the need for medication and of the effect of the medication is a central tenet of medication administration that guides initiation, escalation, and discontinuation of therapy.…”
Section: No Of Patients Median (Iqr)mentioning
confidence: 99%
“…Existe un estudio prospectivo que concluye que si el volumen es alto (>10 ml) aspiración c\2 horas o más a menudo (20) . Respecto a los sistemas de drenajes de secreciones se ha demostrado que disminuye la incidencia de NAVM de comienzo precoz en pacientes con una duración de la ventilación mecánica > 72 horas, pero no hay disminución de la mortalidad, de la estancia en UCI ni de los días de ventilación mecánica (3,5,6,8,9,10,(16)(17)(18)20) . En cuanto a la utilización de sistemas cerrados o abiertos no encuentran diferencias en relación a NAVM pero sí se habla de ventajas e inconvenientes como que el abierto está asociado a desaturación arterial e inestabilidad hemodinámica y el cerrado mayor colonización y es más caro (21)(22)(23) .…”
Section: Nº 38 Abril 2015unclassified
“…9. Se recomienda la desinfección con antiséptico como la clorhexidina 0.12-2% cada 8 horas (8)(9)(10)(11)(12)(13)16,18,26) .…”
Section: Humidificadores E Intercambiadores De Calor-humedad: Todos Lunclassified
See 1 more Smart Citation